Flavonoid Compounds Contained in Epimedii Herba Inhibit Tumor Progression by Suppressing STAT3 Activation in the Tumor Microenvironment - Pan, Cheng; Fujiwara, Yukio; Horlad, Hasita; Shiraishi, Daisuke; Iriki, Toyohisa; Tsuboki, Jyunko; Ikeda, Tsuyoshi; Komohara, Yoshihiro (Frontiers in Pharmacology, 2020)
M2-like tumor-associated macrophages (TAMs) in the tumor tissues promote tumor progression by various mechanisms and represent possible targets of antitumor therapy. In the present study, we tested whether compounds from Epimedii Herba inhibit macrophage polarization to the M2/protumorigenic phenotype and prevent tumor progression, using human monocyte-derived macrophages (HMDMs) and an animal sarcoma model. Four Epimedii Herba-derived flavonoid compounds, namely, limonianin, epimedokoreanin B, icaritin, and desmethylicaritin, inhibited CD163 expression and interleukin (IL)-10 production, which are known M2 markers, suggesting that these compounds inhibit M2 polarization. Among these compounds, epimedokoreanin B and limonianin suppressed STAT3 activation in HMDMs. Notably, epimedokoreanin B also suppressed cell proliferation by blocking STAT3 activation in Saos-2 human sarcoma and LM8 mouse sarcoma cell lines. Furthermore, oral administration of epimedokoreanin B inhibited tumor growth in an LM8 tumor-bearing murine model. These results indicate that Epimedii Herba and Epimedii Herba-derived compounds, such as epimedokoreanin B, may be potentially new agents that can be used for the treatment and prevention of various malignant tumors. They may also be promising compounds for targeting the tumor microenvironment by inhibiting M2 polarization of the TAMs.